The marine invasive seaweeds Asparagopsis armata and Sargassum muticum as targets for greener antifouling solutions - Pinteus, Susete (2020)
Biofouling is a complex phenomenon that affects all maritime dependent industries. The accumulation of both micro and macro-organisms in immerged structures increases significantly the maintenance expenses, and thus the use of antifouling substances is inevitable. Although with recognized antifouling properties, the available antifouling coatings are known to induce negative impacts in aquatic ecosystems. Therefore, greener alternatives are urgently required. Living underwater, marine organisms are prone to biofouling and some have developed strategies to defend themselves against undesirable organisms, which include the production of bioactive substances. As a result, marine organisms are promising sources of natural antifouling substances. Within this framework, the marine invasive seaweeds Sargassummuticumand Asparagopsis armatawere addressed for antifouling compounds biodiscovery. Both seaweeds revealed antifouling properties against microfoulers, namely algicidal and anti-biofilm activities; however Asparagopsis armata stand out for its capacity to inhibit marine bacteria and microalgae growth, to decrease biofilm formation, and for acting as a neurotransmitter disruptor through the inhibition of acetylcholinesterase activity. By addressing invasive species, the problematic of the biological material supply for industrial purposes is surpassed while mitigating the negative impacts of invasive species through specimen's collection.